North Atlantic Regional Water Resources Study. Main Report - CORPS OF ENGINEERS NEW YORK NORTH ATLANTIC DIV (1972)
The Coordinating Committee of the North Atlantic Regional Water Resources Study used a multiple objective planning process to consider alternative objectives, needs, devices, benefits and costs and to develop a 50- year management program for the Region's water and related land resources. The Regional Program, and the conclusions and recommendations of the Coordinating Committee are presented in this Report with a description of the procedures and information used in deriving these results. The North Atlantic Region (NAR) includes the District of Columbia and all or portions of 13 states: Maine, New Hampshire, Vermont, New York, Massachusetts, Connecticut, Rhode Island, Pennsylvania, New Jersey, Delaware, Maryland, West Virginia and Virginia. The NAR extends 1,000 miles from the St. John River Basin in northern Maine to the James River Basin in the southern portion of Virginia. The Region generally extends 200 miles westward from the Atlantic Ocean for its entire length and has 172,586 square miles of land and water surface, or about five percent of the Nation. For planning purposes, the Region has been divided into 21 hydrologically defined areas that range from large river basins such as the Connecticut, Hudson, Delaware, Susquehana and Potomac, to small coastal drainages such as those of Area 13 that includes New York City and Long Island. See also Annex 1 ADA036617. Errata sheet inserted.